Pengaruh Tekanan Uap Boiler Kecil terhadap Kinerja Mekanis Robinson Engine pada Tekanan Maksimum 2,5 bar - Hamdani, Hamdani; Jufrizal, Jufrizal; Idris , Muhammad (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study analyzes the effect of steam pressure variations from a small boiler on the mechanical performance of a Robinson Engine at a maximum pressure of 2.5 bar. A quantitative experimental method was applied with four pressure variations (1.0, 1.5, 2.0, and 2.5 bar). Performance parameters measured included rotational speed, torque, and power, with LPG fuel and water volume maintained as control variables. Results show a significant positive relationship between steam pressure and engine speed; increasing pressure from 1.0 to 2.5 bar raised the speed from 526.2 to 975.6 rpm. These findings highlight the dominant role of steam pressure in engine performance and provide initial quantitative data for developing micro-scale renewable energy-based power plants.